2022
DOI: 10.1108/jwam-07-2022-0043
|View full text |Cite
|
Sign up to set email alerts
|

Time to tell a different story? Positive and negative follower perceptions of their leaders' storytelling

Abstract: PurposeDefying conventional wisdom, leaders' storytelling may have ambiguous and even negative effects on followers. Build upon transformational leadership and leader-member exchange theory, the intention-perception model of storytelling in leadership provides a framework to systematically explain when and why unintended effects of storytelling happen. Despite its theoretical and practical relevance, a quantitative evaluation of the model's main assumptions, and particularly of followers' perceptions of leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…10.51460/baebd.1346897 Sayfa | 1393 that storytelling is a critical leadership skill. As a result of the study conducted by Stark and Reif (2022), it is seen that individuals' perception of the story and the level of meeting their needs are more important than the effective storytelling skills of the leaders. In the studies conducted by Danso and Larsson (2008), Denning (2011), Headrick and Guramatunhucooper (2022), Mladkova (2013), Müceldili and Duran (2022), Pelenk et al (2022), and Thompson (2018), the leadership of managers It has been revealed that there is a positive relationship between storytelling skills and storytelling skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10.51460/baebd.1346897 Sayfa | 1393 that storytelling is a critical leadership skill. As a result of the study conducted by Stark and Reif (2022), it is seen that individuals' perception of the story and the level of meeting their needs are more important than the effective storytelling skills of the leaders. In the studies conducted by Danso and Larsson (2008), Denning (2011), Headrick and Guramatunhucooper (2022), Mladkova (2013), Müceldili and Duran (2022), Pelenk et al (2022), and Thompson (2018), the leadership of managers It has been revealed that there is a positive relationship between storytelling skills and storytelling skills.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it is revealed that the stories told at school have a positive effect on the employees and that storytelling is a critical leadership skill. As a result of the study conducted by Stark and Reif (2022), it is seen that individuals' perception of the story and the level of meeting their needs are more important than the effective storytelling skills of the leaders. According to the findings of the study, having storytelling skills, being a good observer and having a strong memory appear as important storyteller leadership competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Positive and negative follower perceptions of their leaders' storytelling”. They find that “the better a leader's story [meets] followers' needs (need-supply fit), the more adequate the input load transported by the story (story load), and the more positive followers' appraisal of their leader's story (story appraisal), the more positive followers' affective reactions and effects of storytelling (transformation, leader-member exchange quality, and trust in the leader)” (Stark and Reif, 2023). These concepts are particularly pertinent to wider change efforts in organisational development and the stories used around applied methods.…”
mentioning
confidence: 99%
“…The sixth paper, drawing again on the power of narrative for change work, is by Stark and Reif (2023), and is entitled "Time to tell a different story? Positive and negative follower perceptions of their leaders' storytelling".…”
mentioning
confidence: 99%